A complicated case of mitral valve disease. - James, S E (1985)
A patient with rheumatic mitral stenosis and previous cerebral embolism had a myocardial infarction during cardiac catheterisation. She later developed severe mitral regurgitation one year after open valvotomy and at valve replacement was found to have a papillary tumour of the mitral valve. Unexplained low cardiac output occurred four days after operation. Postmortem examination showed thrombotic occlusion of the xenograft prosthesis, a complication not previously seen with tissue valves. Both of these rare events were suggested by the patient's clinical course and could have been diagnosed with cross sectional echocardiography.